2014
DOI: 10.1136/vr.102574
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of detection of respiratory viruses in nasal swabs from calves in Ireland: a retrospective study

Abstract: A retrospective analysis was conducted to investigate the prevalence and seasonality of bovine viral diarrhoea virus (BVDV), bovine coronavirus (BoCV), bovine herpesvirus-1 (BoHV-1), bovine respiratory syncytical virus (BRSV) and parainfluenza virus-3 (PI3V) in calves (aged three months and below) in Ireland. Results from real-time PCR testing, including cycle threshold values, conducted on nasal swabs (single or pooled) submitted from 1364 respiratory disease outbreaks between January 1, 2008 and December 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 38 publications
5
56
3
2
Order By: Relevance
“…It is of interest to notice that ECoV qPCR-positive horses were only detected during the winter and spring months, which is in agreement with the detection of BCoV in nasal secretions of calves with bovine respiratory disease (O'Neill and others 2014). Further, the majority of the ECoV outbreaks reported in the literature occurred during the cold months of the year (Oue and others 2013, Pusterla and others 2013).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…It is of interest to notice that ECoV qPCR-positive horses were only detected during the winter and spring months, which is in agreement with the detection of BCoV in nasal secretions of calves with bovine respiratory disease (O'Neill and others 2014). Further, the majority of the ECoV outbreaks reported in the literature occurred during the cold months of the year (Oue and others 2013, Pusterla and others 2013).…”
supporting
confidence: 80%
“…BCoV has been shown in one recent study (O'Neill and others 2014) to be the most frequently detected partner virus found in combination with other respiratory viruses in nasal secretions from calves associated with respiratory disease outbreaks. Out of the 17 ECoV qPCR-positive horses, nine (52.9 per cent) showed coinfection with either EHV-4, EIV, ERBV or S equi subspecies equi .…”
mentioning
confidence: 99%
“…multocida ( n = 56) as previously described [14,15,16,17]. Reverse transcriptase PCR analyses to identify BRSV (n = 133) and BPIV-3 (n = 133) were also performed individually on samples taken from the paranasal sinuses, trachea and lungs as previously described [18]. DNA or RNA extracted from laboratory strains of the target organisms using commercial DNA or RNA isolation kits (for M .…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial pathogens frequently associated with BRD include Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis (GAGEA et al, 2006;GRIFFIN et al, 2010;FRANCOZ et al, 2015). Viral agents commonly identified in cattle with BRD are bovine viral diarrhea virus (BVDV), bovine respiratory syncytial virus (BRSV), bovine herpesvirus -1 (BoHV-1), bovine parainfluenza virus-3 (BPIV-3), and bovine coronavirus, BoCV (GAGEA et al, 2006;O'NEILL et al, 2014;FRANCOZ et al, 2015). In most cases, viral agents are considered as primary or predisposing factors to bacterial agents, due to the immunodepressive effects on the affected animal.…”
Section: Introductionmentioning
confidence: 99%